Global Contagion of Investor Sentiment during the US Subprime Crisis: The Case of the USA and the Region of Latin America - Talbi, Mariem; Halima, Amel Ben (International Journal of Economics and Financial Issues, 2019)
This paper contributes to a growing body of literature studying investor sentiment. Sentiment measures for USA investors are constructed from commonly cited sentiment indicators using the first principle component method. We then examine if the investor sentiment propagates among the markets and how the interdependency through the propagation changes during the course of the US subprime crisis. We adopt a bivariate Conditional dynamic correlation generalized autoregressive conditional heteroscedasticity (DCC GARCH) model, and use a sample of the global markets for the following area: USA and Latin America, in our investigation between ‘‘turbulent’’ and ‘‘tranquil’’ periods in the financial markets . Our results identify that: (1) a long-run equilibrium relationship existed between investor sentiment in the US and other global markets during the subprime crisis period; (2) a global contagion of investor sentiment occurred from the US market on September 15, 2008 to other developed countries; and (3) the global markets are all interrelated. (4) We find that sentiment tends to be a more important determinant of returns in the run-up to crisis than at other times. Keywords: Subprime crisis, Investor sentiment, Contagion, Bivariate DCC GARCH model JEL Classifications: G01, G11, G15, C53 DOI: https://doi.org/10.32479/ijefi.7985